2009
DOI: 10.1091/mbc.e08-01-0099
|View full text |Cite
|
Sign up to set email alerts
|

SubtelomericACS-containing Proto-silencers Act as Antisilencers in Replication Factors Mutants inSaccharomyces cerevisiae

Abstract: Subtelomeric genes are either fully active or completely repressed and can switch their state about once per 20 generations. This meta-stable telomeric position effect is mediated by strong repression signals emitted by the telomere and relayed/enhanced by weaker repressor elements called proto-silencers. In addition, subtelomeric regions contain sequences with chromatin partitioning and antisilencing activities referred to as subtelomeric antisilencing regions. Using extensive mutational analysis of subtelome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Our results suggest that the links between replication timing and high-order genome organization, also observed in other organisms, may have been conserved throughout evolution [28], [41], [75], [76].…”
Section: Discussionsupporting
confidence: 69%
“…Our results suggest that the links between replication timing and high-order genome organization, also observed in other organisms, may have been conserved throughout evolution [28], [41], [75], [76].…”
Section: Discussionsupporting
confidence: 69%
“…URA3-tel, GF2, GF3, GF6, GF9, GF44, GF46, GF61, GF6ΔSTAR, GF6ΔACS and GF44ΔACS showed very similar levels of %FOA R in BY4742 cells as compared to the previously used W303 strain [4], [24], [25]. In addition, the prototype URA3-tel construct recapitulated the silencing defects observed in sas2, sas3, orc2-1, orc5-1, mcm5-461, cdc6-1, cdc45-1 and cdc7-1(sas1) (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…The insertions between URA3 and the telomeric repeat add 145-900 base pairs in different constructs as compared to URA3-tel. Several studies have shown that the telomeric silencing for these and other constructs does not directly correlate to the distance from the telomeres [2], [3], [4], [24], [25]. Instead, silencing is discontinuous and is strongly influenced by the nature and the positions of different regulatory elements [2], [26].…”
Section: Resultsmentioning
confidence: 97%
“…Cross-linked chromatin was sheared, extracted and immunoprecipitated with a mixture of anti-MCM2 and anti-MCM5 antibodies (Santa Cruz). We have found that this mixture of anti-peptide antibodies is more efficient in recovery of origin DNA as compared to the individual antibodies used alone [40], [41]. Finally, the immunoprecipitated DNA was analyzed by quantitative PCR with primers for ARS1 and ARS305 .…”
Section: Resultsmentioning
confidence: 99%